2019
DOI: 10.1155/2019/6456141
|View full text |Cite
|
Sign up to set email alerts
|

Our Experience with Iatrogenic Ureteric Injuries among Women Presenting to University College Hospital, Ibadan: A Call to Action on Trigger Factors

Abstract: Background. Ureteric injuries leading to ureterovaginal fistula (UVF) is less common than vesicovaginal fistula, as a cause of urinary incontinence. Recently, there is a surge in the number of UVF cases presenting to University College Hospital (UCH) following a caesarean delivery. The urogynaecology unit at UCH is at the forefront of providing surgical repair for women with all forms of genitourinary fistulas. We describe our experience with managing UVF arising from ureteric injury. Methods. A retrospective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 20 publications
1
17
0
Order By: Relevance
“…The left ureteric injury occurred frequently following surgery, the left ureter bringing it closer to the pelvic structures, the left ureter more to iatrogenic injures. 5 In our study the left ureteric injury occurred frequently 66%. The placement of ureteric stents preoperatively wasn't decreasing the ureteric injuries risk as demonstrated by Kuno et al In fact, the presence of the ureteric stents may actually make the ureter less pliable and more rigid thereby increasing the injury risk during dissection to mobilize it.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…The left ureteric injury occurred frequently following surgery, the left ureter bringing it closer to the pelvic structures, the left ureter more to iatrogenic injures. 5 In our study the left ureteric injury occurred frequently 66%. The placement of ureteric stents preoperatively wasn't decreasing the ureteric injuries risk as demonstrated by Kuno et al In fact, the presence of the ureteric stents may actually make the ureter less pliable and more rigid thereby increasing the injury risk during dissection to mobilize it.…”
Section: Discussionsupporting
confidence: 49%
“…Shoemaker introduced the Ileal ureter replacement and was popularized by Goodwin et al 19 Some studies found high success rate with ureteroneocystostomy. 5 In all injuries of ureteric percutaneous nephrostomy drainage recovered of ureter in 80% cases. 10 Lask et al ureteric injuries patients under percutaneous nephrostomy, out of these 16 (80%) had complete spontaneous recovery of injured ureter after 14-66 days.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…during cesarean delivery or hysterectomy), and trauma. Prolonged obstructed labor is most prevalent; however, an increasing proportion of genital fistula is iatrogenic …”
Section: Introductionmentioning
confidence: 99%
“…15 In contrast to that reported by Olatunji et al in Nigeria where caesarian delivery was the leading gynecologic surgery, in our study, hysterectomy was reported in 61% Globally, iatrogenic ureteric trauma is the common cause of ureteral injury with gynecologic surgery being the most causative event. 16 According to the laterality, the lesion was unilateral in 95% with the left ureter 72% of cases. In the study of Chalya et al in Tanzania, the left side was also reported in 70% of cases.…”
Section: Discussionmentioning
confidence: 97%